Do Not Skip the Retroflexion: A Case of Disseminated Anorectal Mucosal Melanoma. Issue 2 (3rd February 2021) - Chittajallu, Vibhu; Simons-Linares, Carlos Roberto; Oshilaja, Olaronke; Chahal, Prabhleen
ABSTRACT: Less than 4% of melanomas are of mucosal origin, with primary anorectal mucosal melanomas comprising a small subset. Mucosal melanomas are often diagnosed at an advanced stage due to delay in patient presentation and obscured tumor origins leading to a more aggressive behavior and less favorable prognosis when compared with cutaneous melanomas. We present a case of metastatic anorectal mucosal melanoma with a negative colonoscopy 1 year earlier.